Public health advocacy strategies to influence policy agendas: lessons from a narrative review of success in trade policy - Belinda Townsend; Brigitte Frances Tenni; Sharni Goldman; Deborah Gleeson (BMC, 2023)
Abstract Background Despite accumulating evidence of the implications of trade policy for public health, trade and health sectors continue to operate largely in silos. Numerous barriers to advancing health have been identified, including the dominance of a neoliberal paradigm, powerful private sector interests, and constraints associated with policymaking processes. Scholars and policy actors have recommended improved governance practices for trade policy, including: greater transparency and accountability; intersectoral collaboration; the use of health impact assessments; South-South networking; and mechanisms for civil society participation. These policy prescriptions have been generated from specific cases, such as the World Trade Organization's Doha Declaration on TRIPS and Public Health or specific instances of trade-related policymaking at the national level. There has not yet been a comprehensive analysis of what enables the elevation of health goals on trade policy agendas. This narrative review seeks to address this gap by collating and analysing known studies across different levels of policymaking and different health issues. Results Sixty-five studies met the inclusion criteria and were included in the review. Health issues that received attention on trade policy agendas included: access to medicines, food nutrition and food security, tobacco control, non-communicable diseases, access to knowledge, and asbestos harm. This has occurred in instances of domestic and regional policymaking, and in bilateral, regional and global trade negotiations, as well as in trade disputes and challenges. We identified four enabling conditions for elevation of health in trade-related policymaking: favourable media attention; leadership by trade and health ministers; public support; and political party support. We identified six strategies successfully used by advocates to influence these conditions: using and translating multiple forms of evidence, acting in coalitions, strategic framing, leveraging exogenous factors, legal strategy, and shifting forums. Conclusion The analysis demonstrates that while technical evidence is important, political strategy is necessary for elevating health on trade agendas. The analysis provides lessons that can be explored in the wider commercial determinants of health where economic and health interests often collide.